Apropriação do lavrado pelo turismo : lago do Robertinho - Thowinsson, Karina Yohanna Alarcon (2019)
The state of Roraima is located in the extreme north of Brazil has presented itself as a tourist attraction by the exuberant nature that encompasses it. Many companies have been created to take advantage of the opportunities given the demand for recreation and leisure activities associated with tourism. In the capital, Boa Vista, it is possible to find enterprises that use lakes as an option to enjoy leisure. It is known that every new building produces impacts, even when they are in regions that use nature as attractive. The study area consists of the Lago Robertinho project located in Boa Vista, 40 km from the BR-174 and 20 km from Boa Vista / Pacaraima on the left close of the Murupú River. This place is renowned for scenic beauty regionally recognized for attracting visitors by hosting a company that offers adventure and leisure activities around a lake. In this sense, the general objective of this dissertation is to analyze the feelings, attitudes and behaviors of visitors, in relation to the environmental variable, taking as an empirical object the venture Lago do Robertinho. For that, a qualitative-quantitative research was conducted, with interviews to the visitors of the enterprise, employees and manager with methodological and data triangulation. A bibliographic survey was carried out on the ecological dynamics of the Lake and its characterization, use of cartographic data of IBGE and use of image of Remote Sensors that underwent atmospheric and radiometric corrections. Software were used to compile the thematic maps of location, slope, elevation and main stretches of access to the lake. Therefore, the research shows that the environmental impacts resulting from the presence of solid residues, damage to vegetation, soil erosion, irregular constructions and irregular trails are of low complexity, since management by the lake takes care of this, except for the concern with guidelines directed to visitors. As for the feeling of the visitors in relation to the lake, it occurs, mainly, in the pursuit of leisure, pleasure and tranquility. The age group of people who attend the venture turns to the young public and the attention paid refers to the landscape and the attractions. However, it is necessary to use guidelines with the use of signs (signs), in the search of the visitors' sensitization in relation to the susceptible environmental impacts that generate negativity to the development and conservation of the landscape.